Maksim Kesantunan Berbahasa Yang Terkandung Pada Teks Negosiasi Yang Disusun Oleh Siswa Kelas X Smk Ibnu Khaldun Panambangan Kab. Cirebon - Khofifah Indah Baitul Jannah; Emah Khuzaemah; Itaristanti (Mutiara: Multidiciplinary Scientifict Journal, 2023)
Politeness is a form of ethics or manners for using language in communication used by the public orally and in writing, in this case the use of language that pays little attention to politeness in the negotiating texts prepared by students. The purpose of this study is to describe the politeness maxims contained in the negotiating texts prepared by students. This research uses a type of qualitative research with a descriptive qualitative research design. The technique of data collection, namely the first is using the listening method with the free involvement speaking technique, note taking technique. The instruments used in this study were data cards and student analysis questionnaires. The validity of the data in this study uses triangulation of data sources. Then the data analysis technique uses the pragmatic equivalent method. The results of this study resulted in 80 utterances of language politeness analysis in negotiating texts composed by class X students of SMK Ibnu Khaldun Panambangan, Cirebon Regency. The results of the analysis consist of 50 utterances of politeness, starting from 11 maxims of wisdom, 6 maxims of acceptance, 10 maxims of generosity, 7 maxims of humility, 10 maxims of conformity, and 6 maxims of sympathy. Based on the flouted maxims, there are 30 utterances, starting from wisdom maxim 7, acceptance maxim 3, generosity maxim 6, modesty maxim 3, compatibility maxim 10, and sympathy maxim 1.